Students' Mathematical Creative Thinking Ability Judging from Self-Regulated Learning in MiC Learning with an Open-Ended Approach - Hermawan, Jody Setya; Asikin, Mohammad; Dwidayati, Nur Karomah (Unnes Journal of Mathematics Education Research, 2021)
The purpose of this study is to analyze the mathematical creative thinking ability of class VIII students in terms of Self-Regulated Learning. This research method is mixed-method research with a sequential explanatory design. The research population is class VIII SMP Futuhiyyah Mranggen Academic Year 2020/2021. The sampling technique of self-regulated learning uses simple random sampling by taking 6 subjects. The results show that students with high Self-Regulated Learning can have a smooth flow of thought, can produce uniform ideas, can give answers that are different or unusual from the others, and can develop, add, and enrich an idea. Students with Self-Regulated Learning can have a smooth flow of thought and can develop, add, and enrich an idea. Students with low Self-Regulated Learning are only able to have a smooth flow of thought.